Determining the Best Location for a New Retail Branch with the Weighted Aggregated Sum Product Assessment Method - Aldy; Hendrawan, Jodi; Putra, Hardiansyah (Cattleya Darmaya Fortuna, 2024)
Determining a strategic location for the opening of a new branch is an important decision in the development of the retail business. Choosing the right location can increase competitiveness and business success, while choosing the right one can pose a risk of loss. This article aims to evaluate and determine the best location for a new retail branch using the Weighted Aggregated Sum Product Assessment (WASPAS) method. The WASPAS method was chosen because of its ability to combine two multi-criteria approaches, namely the Weighted Sum Model (WSM) and the Weighted Product Model (WPM), which allows for a more comprehensive assessment of various location determinants, such as demographics, accessibility, operational costs, and market potential. Through a case study conducted on a company, the results of this study show that the WASPAS method can provide accurate and reliable recommendations in determining the best location for a new branch. The resulting recommendations are expected to support better strategic decision-making in the development of retail networks.